Spectrum of the Anomalous Microwave Emission in the North Celestial Pole with WMAP 7-Year Data. (19th December 2012) - Bonaldi, Anna; Ricciardi, Sara
Abstract : We estimate the frequency spectrum of the diffuse anomalous microwave emission (AME) on the North Celestial Pole (NCP) region of the sky with the Correlated Component Analysis (CCA) component separation method applied to WMAP 7-yr data. The NCP is a suitable region for this analysis because the AME is weakly contaminated by synchrotron and free-free emission. By modeling the AME component as a peaked spectrum we estimate the peak frequency to be 21.7 ± 0.8 GHz, in agreement with previous analyses which favored ν p < 23 GHz. The ability of our method to correctly recover the position of the peak is verified through simulations. We compare the estimated AME spectrum with theoretical spinning dust models to constrain the hydrogen density n H . The best results are obtained with densities around 0.2–0.3 cm −3, typical of warm ionised medium (WIM) to warm neutral medium (WNM) conditions. The degeneracy with the gas temperature prevents an accurate determination of n H, especially for low hydrogen ionization fractions, where densities of a few cm −3 are also allowed.